Antibodies against MYC-Associated Zinc Finger Protein: An Independent Marker in Acute Coronary Syndrome? - Ernst, Diana; Widera, Christian; Baerlecken, Niklas T.; Schlumberger, Wolfgang; Daehnrich, Cornelia; Schmidt, Reinhold E.; Gabrysch, Katja; Wallentin, Lars; Witte, Torsten (Frontiers in Immunology, 2017)
Introduction Atherosclerosis is considered the pathophysiology underlying cardiovascular (CVD), cerebrovascular, and peripheral vascular diseases. Evidence supporting an autoimmune component is emerging, with imaging studies correlating MYC-associated zinc finger protein antibody (MAZ-Ab) optical density (OD) with plaque activity. This study compares MAZ-Ab OD on ELISA testing among patients presenting with acute coronary syndromes (ACSs) to healthy controls and investigates the association of MAZ-Ab to traditional CVD risk factors. Methods Patients admitted with ACSs between August 2007 and July 2011 were included. Serum samples taken at presentation were retrospectively tested for MAZ-Ab and compared with serum from healthy volunteers with no CVD risk factors. Large-scale assessment of post-ACS prognostic relevance was performed using the established PLATO cohort. Results In total 174 ACS patients and 96 controls were included. Among ACS patients, median MAZ-Ab OD was higher compared with controls (0.46 vs. 0.27; p = 0.001). Although the majority of ACS patients (116/174; 67%) had suffered from a ST-elevation myocardial infarction, no significant differences in MAZ-Ab titers were evident between ACS subtypes (p = 0.682). No associations between MAZ-Ab OD and conventional CVD risk factors were identified. Large-scale testing revealed no prognostic stratification regarding reinfarction (OR 1.04 [95% CI: 0.94–1.16]; p = 0.436). Conclusion MAZ-Ab OD was higher or all ACS phenotypes compared with controls. Given current understanding of MAZ-Ab function, these findings support an autoimmune component to CVD independent of conventional risk factors and indeed the extent of end-organ damage.